PDL1 expression is a poor-prognosis factor in soft-tissue sarcomas. (4th March 2017) - Bertucci, François; Finetti, Pascal; Perrot, Delphine; Leroux, Agnès; Collin, Françoise; Le Cesne, Axel; Coindre, Jean-Michel; Blay, Jean-Yves; Birnbaum, Daniel; Mamessier, Emilie
ABSTRACT: Soft-tissue sarcomas (STS) are a group of rare, heterogeneous, and aggressive tumors, with high metastatic risk and relatively few efficient systemic therapies. In the quest for new treatments, the immune system represents an attractive therapeutic target. Recently, PD1/PDL1 inhibitors showed very promising results in patients with solid tumors. PDL1 expression has been rarely studied in STS, in small series only, by using immunohistochemistry (IHC), and with non-concordant prognostic implications. Here, we have analyzed PDL1 mRNA expression in 758 clinical STS samples retrospectively profiled using DNA microarrays and RNAseq, and searched for correlations with clinicopathological variables including metastasis-free survival (MFS) after surgery. PDL1 expression was heterogeneous across the samples. PDL1-high samples (41%) were more frequently leiomyosarcomas and liposarcomas, and showed more frequently a complex genetic profile and a high-risk CINSARC signature. No correlation existed with other clinicopathological features such as tumor site, depth, and pathological tumor grade and size. In multivariate prognostic analysis, the PDL1-high class was associated with shorter MFS, independently of the pathological type and the CINSARC signature. Analysis of correlations with biological factors suggested the existence in tumors of the PDL1-high class of a strong and efficient cytotoxic T-cell response, however associated with some degree of T-cell exhaustion and negative regulation. In conclusion, we show that PDL1 expression refines the prediction of metastatic relapse in operated localized STS, and that PD1/PDL1 blockade holds potential to improve patient survival by reactivating inhibited T cells to increase the antitumor immune in PDL1-high tumors.